Atherogenic Dyslipidemias: Unmet Needs and the Therapeutic Potential of Emerging and Novel Approaches and Drugs - Alessandra Romandini; Damiano Baldassarre; Stefano Genovese; Stefano Capri; Giulio Pompilio; Marco Scatigna; José Pablo Werba (MDPI AG, 2023)
Innovative lipid-modifying agents are valuable resources to improve the control of atherogenic dyslipidemias and reduce the lipid-related residual cardiovascular risk of patients with intolerance or who are not fully responsive to a consolidated standard of care (statins plus ezetimibe). Moreover, some of the upcoming compounds potently affect lipid targets that are thus far considered "unmodifiable". The present paper is a viewpoint aimed at presenting the incremental metabolic and cardiovascular benefits of the emerging lipid-modulating agents and real-life barriers, hindering their prescription by physicians and their assumption by patients, which need to be worked out for a more diffuse and appropriate drug utilization.